도시대기 부유분진중의 중금속 오염도에 관하여 : 서울시 신촌지역을 중심으로 - 주의조 (연세대학교 보건대학원, 1987)
[한글] 오늘날 대기오염으로 인한 피해는 이들 개개의 가스나 부유입자상물질의 피해보다는 가스와 액체나 고체 미립자와 상호간에 작용하거나 타 오염물질과 공존시 복합적인 반응을 일으켜 그들 성분이 건강에 가장 나쁜 영향을 줄 가능성이 높은 것으로 보고되었다. 그 동안 부유분진 중의 중금속 오염도에 관하여는 비교적 많은 연구가 보고되고 있으나, 서울시 몇몇 지역의 중금속 오염도를 측정하여 그 분포를 파악한 연구가 주류이며 중금속간의 상관을 조사한 연구는 약간 있을 따름이다. 이번 조사에서는 서울시 대기중 부유분진 중의 중금속 오염도 양상과 오염물질과의 상관을 조사하며 중금속 오염도 양상의 파악과 대기중의 중금속과 오염물질들의 발생원을 추정하고자 하였다. 서울시 신촌동을 대상으로 대기오염이 일년 중 가장 심한 겨울철(86년 1,2월)을 택하여 high volume air sampler로 부유분진을 채취하고 가스상 오염물질은 대기오염 자동 측정기를 사용하였으며 이 시료를 원자흡광분석기와 IC7로 측정하여 다음과 같은 결과를 얻었 다. 1) 조사기간중의 대기오염도는 SO**2, TSP가 각각 135ppb, 167㎎/㎡ 연간 대기환정기준을 초과하였고 기타 오염물질은 기준치 이하인 것으로 나타났다. 2) 서울시 대기중의 중금속은 대부분 연도에 따라 점차 감소하는 경향을 보이고 있으나 Ni만은 증가하는 경향을 보이고 있었다. 3) 중금속 오염도간의 상관이 높은 군으로는 V, Fe, Zn가 서로 0.7이상의 높은 상관을 보였으며 Pb는 Zn, Fe와 상관이 높은 반면 V과는 비교적 낮은 상관을 보였다. 4) 부유분진 중의 중금속 함유량간에도 V와 Ni이 상관계수 r=0.8557로 매우 높았으며 이는 석유계 연료의 연소로 기인한 것으로 생각되며 그외는 Fe,Pb,Zn등의 서로간의 상관이 높은 군이었으므로 이들은 석탄계 연료의 연소로 인한 것으로 생각된다. 5) SO^^2가 전반적으로 대부분이 증금속류와 상관이 높았으며 특히 Pb와는 r=0.9081의 높은 상관을 보였다. Pb는 SO^^2 이외에도 NOx, CO, TSP와도 상관이 높았다. TSP는 V, Ni군에 비해 Pb와의 상관이 높아 분진의 발생이 석유계 연료연소보다도 석탄계 연료나 자동차 배기분진과의 관련이 높은 것으로 생각된다. 이상의 결과로 보아 대기 부유분진중의 중금속간의 상관 및 타오염물질과의 상관은 오염원에 영향을 받을 것으로 예상되며 서울시의 경우 석유계 연료 소비 증가에 따른 Ni등의 오염도 증가가 예상된다. 또한 각종 오염도 부유분진중의 중금속류의 패턴 변화는 앞 으로 건강과의 관계에도 영향이 클 것이다. 따라서 이 방면의 보다 많은 조사가 있어야 할 것이다. Heavy Metals of Ambient Air Suspended in the Shin Chon Area of Seoul City Ui Jo, Chu Dept. of Environment science Graduate School of Health Science and Management Yonsei University (Directed by Professor Chung Yong, PH.D) In order to investigate the character of air pollution by heavy metals in Seoul city, this study was performed to measure the concentrations of heavy metals of total suspended particulate(T.S.P) and air pollutants such as SO^^2NO^^2 as well as their relationship among various heavy metals and to evaluate the source of heavy metals and to evaluate the source of heavy metals were determined by atomic absorption spectrophotometry. The vanadium was determined by I.C.P emission spectrophotometry. The results are as follow: 1. SO^^2 and T.S.P. concentration were 135ppb and 167㎎/㎥ in average respectively. these were overviolated to the legal environmental standard. Other pollutant NO^^2, CO, and O^^3, however, were lower than standard. 2. While total concentration of heavy metal In the ambient air particulate was gradually decreasing annually. Ni compound has being shown in the tendency increasing. 3. among heavy metals In T.S.P. analysed, the iron was detected at the highest level, 0.905% and the cadmium was the lowest 0.004% respectively in average. 4. V, Fe and Zn compounds were observed to be highly correlated to the levels of air pollution indicator such as SO^^2, NO^^0 and others with their correlation coefficients higher than 0.7. Pb compound was highly correlated to the levels of Zn and Fe, however relatively less correlated to V compound. 5. Among concentrations of heavy metals in the particulates, V and N1 compounds were highly correlated with coefficient of 0.8587; the cause might be imagined with coefficient of 0.8587; the cause might be imagined by the fact of releasing from combustion of fuel oil. Fe, Pb and Zn compounds were highly corrected to SO^^2 concentration. It may be explained by the fact that they are released by the that they are released by combustion of coal. 6. The level of SO^^2 was highly correlated to most of heavy metals(especially correlation coefficient, to Pb compound was 0.9081). Pb compound was also highly correlated to NO^^X, CO and T.S.P. T.S.P. showed higher close correlation to Pb compound than to V and Ni compound. It might be assumed that particulate was mainly produced by combusting coal from space heating and exhausting from vehicle rather than by burning fuel oil. 7. The correlationship between heavy metal content of particulate and their sources should be further investigated including A1, Se, PAH, SO^^4, compounds etc. From the above results, it is concluded that level of heavy metal in the various kinds of fuel and also increased by fuel consumption of various kinds of fuel and also increased by fuel consumption increase, as well. As variation of contents and kinds of heavy metal in ambient air are greatly influenced to human health, further more studies in this field should be all necessity. [영문] In order to investigate the character of air pollution by heavy metals in Seoul city, this study was performed to measure the concentrations of heavy metals of total suspended particulate(T.S.P) and air pollutants such as SO^^2NO^^2 as well as their relationship among various heavy metals and to evaluate the source of heavy metals and to evaluate the source of heavy metals were determined by atomic absorption spectrophotometry. The vanadium was determined by I.C.P emission spectrophotometry. The results are as follow: 1. SO^^2 and T.S.P. concentration were 135ppb and 167㎎/㎥ in average respectively. these were overviolated to the legal environmental standard. Other pollutant NO^^2, CO, and O^^3, however, were lower than standard. 2. While total concentration of heavy metal In the ambient air particulate was gradually decreasing annually. Ni compound has being shown in the tendency increasing. 3. among heavy metals In T.S.P. analysed, the iron was detected at the highest level, 0.905% and the cadmium was the lowest 0.004% respectively in average. 4. V, Fe and Zn compounds were observed to be highly correlated to the levels of air pollution indicator such as SO^^2, NO^^0 and others with their correlation coefficients higher than 0.7. Pb compound was highly correlated to the levels of Zn and Fe, however relatively less correlated to V compound. 5. Among concentrations of heavy metals in the particulates, V and N1 compounds were highly correlated with coefficient of 0.8587; the cause might be imagined with coefficient of 0.8587; the cause might be imagined by the fact of releasing from combustion of fuel oil. Fe, Pb and Zn compounds were highly corrected to SO^^2 concentration. It may be explained by the fact that they are released by the that they are released by combustion of coal. 6. The level of SO^^2 was highly correlated to most of heavy metals(especially correlation coefficient, to Pb compound was 0.9081). Pb compound was also highly correlated to NO^^X, CO and T.S.P. T.S.P. showed higher close correlation to Pb compound than to V and Ni compound. It might be assumed that particulate was mainly produced by combusting coal from space heating and exhausting from vehicle rather than by burning fuel oil. 7. The correlationship between heavy metal content of particulate and their sources should be further investigated including A1, Se, PAH, SO^^4, compounds etc. From the above results, it is concluded that level of heavy metal in the various kinds of fuel and also increased by fuel consumption of various kinds of fuel and also increased by fuel consumption increase, as well. As variation of contents and kinds of heavy metal in ambient air are greatly influenced to human health, further more studies in this field should be all necessity.
환경관리학과/석사